PROBLEMS OF FORMATION AND DISCLOSURE OF INFORMATION ON SEGMENTS IN THE FINANCIAL STATEMENTS OF ORGANIZATIONS (IFRS 8) - B.А. Mukhaeva,; D.D. Yeshpanova, (Academic Journal of Physical and Chemical Sciences, 2019)
The relevance of the study lies in the fact that due to a fundamental revision of the rules of segment reporting in the direction of their adaptation to changing economic conditions and user requirements, it became necessary to analyze the effectiveness of these new rules, identify difficulties in their application in practice and ways to improve them. Despite research in the field of segment reporting, there is currently no method for generating information necessary for preparing segment reporting, which allows companies that are not the flagships of the economy and do not have developed management accounting to effectively solve the problem of providing information on operating segment reporting. In this regard, the article discusses the problems of formation and disclosure of information in the financial statements of organizations, since financial and economic data together with the system of external and internal business conditions of an organization allow analyzing the contribution of each type of activity to the overall result of a company and substantively assessing the functioning of each segment.